Physical, chemical and biological characterization of Sibuti mangrove forest estuary, Sarawak, Malaysia - Saifullah, A. S. M. (2015)
Estuaries are the areas of complex interaction between fresh and saline water. The mangrove estuaries are claimed to be the most productive and considered as the breeding ground for fishery resources. Though, Malaysia is blessed with number of mangrove estuaries, however not adequate research findings are reported about their potentialities. Thus, this study was conducted to investigate the characteristics, plankton diversity and feeding habit of fishes in Sibuti mangrove estuary. Monthly sampling for ecological and biological parameters was conducted from January 2013 to December 2013 and data were pooled into seasons viz., intermediate, dry and wet. The summarised indices from Estuarine Water Quality Index (EWQI), Shannon- Wiener Diversity Index (SWDI) and Estuarine Resource Importance Index (ERII) claimed this estuary as high quality (total index 10.83). The hydrobiological parameters of the estuary followed a seasonal rhythm. The surface water temperature of the estuary ranged from 27.1 to 32.2οC and revealed mesohaline on the basis of salinity ranged from 0.3 to 27.1 PSU. Water of the estuary revealed acidic to alkaline where dissolved oxygen (DO), total dissolved solids (TDS) and light extinction coefficient (LEC) were observed ranging from 1.94 to 6.71 mgL-1, 0.5 to 43.9 mgL-1 and 1.71 to 6.71 respectively. The chlorophyll a concentration of the surface water ranged from 0.002 to 0.348 mg m-3. Primary productivity (PP) ranged from 0.20gCm-3hr-1 to 0.74gCm-3hr-1 (0.53±0.15gCm-3hr-1) with its higher mean in the intermediate season (0.60±0.08 gCm-3hr-1) and the lower in the wet season (0.35±0.12 gCm-3hr-1). Nitrate, phosphate, ammonium and silica concentrations ranged from 0.40 to 3.53 mgL-1, 0.01 to 1.92 mgL-1, 0.06 to 1.24 mgL-1 and 1.7 to 3.47mgL-1 respectively. Seasonality exerted significant variation in surface water temperature, salinity, TDS, conductivity and ammonium. One hundred two (102) species of phytoplankton under 43 genera were recorded from Sibuti mangrove estuary including 6 species of Cyanophyta, 4 species of Chlorophyta, 63 species of Diatom and 29 species of Dinoflagellate. Mean abundance of phytoplankton ranged from 5694 to 88890 cellsL-1 over the study period with its higher value in the dry season. Species recorded from the estuary, were dominated by Pleurosigma normanii, Coscinodiscus sp, Coscinodiscus centralis, Coscinodiscus granii, Dinophysis caudata, Ceratium carriense, Ceratium fusus and Ceratium lineatum. Abundance of phytoplankton demonstrated positive correlation with chlorophyll a (r=0.69, p=0.01), ammonium (r=0.64, p=0.01) and silica (r=0.64, p=0.01). A total of 54 forms of zooplankton belonging to diverse groups viz., copepod (35), chaetognatha (1), decapoda (1), amphipoda (1), mysid (1), cladocera (1), ostracoda (1), rotifer (1), tintinnid (1), apendicularia (1), doliolid (1), medusa (1), mollusc (2) and larvae, nauplii and fish eggs (6) were recorded form the estuary. The majority of zooplankton was occupied by copepod (73.58%) and was dominated by Acartia spp.(calanoida), Oithona spp. (cyclopoida) and Euterpina spp. (harpacticoida). Abundance of zooplankton ranged from 1419.58- 3121.59 ind. m-3 and maximum was observed in the intermediate season while minimum in the wet season. Species diversity (H́) of zooplankton ranged from 1.62-2.61 and there was revealed no seasonal or site specific variation. Zooplankton abundance showed positive correlation with phytoplankton (r=0.66, p=0.01) and chlorophyll a (r= 0.73, p=0.01). A total of 997 stomachs of 12 species of fishes under 9 genera namely Arius maculatus, Arius caelatus, Arius truncatus, Hexanematichthys sagor, Setipinna melanochir, Setipinna breviceps, Setipinna taty, Coilia dussumieri, Opisthopterus tardoore, Ilisha elongata, Nibea saldado and Otolithes ruber were investigated for the purpose of getting insight of feeding habits of the fishes of the estuary. Empty stomach consisted of the largest portion of investigated stomachs and poor feeding was common all over the study period. Crustacean dominated by shrimps were found as the most preferred food of the fishes followed by miscellaneous (appendages, detritus, plant parts) and molluscs. Feeding habit of fishes was found different in various length group as well as seasons. A cluster analysis based on dietary overlaps and dominant food consumption criteria, revealed four feeding guilds viz., shrimp feeder, gastropod and bivalve feeder, fish and shrimp feeder and detritus (plant part and sand-mud) and shrimp feeder. The results depicting estuarine characteristics, diverse primary consumer (phytoplankton), secondary consumer (zooplankton) and feeding habit of fishes and the correlation among them exerted an interlocking pattern, which demonstrated the interdependency of the variables towards functioning of the estuary.